2020
DOI: 10.5539/ass.v16n8p20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Media Application in Promoting Motivation and Listening Skill of Iraqi EFL Learners: A Skype-Based Study

Abstract: This study seeks to investigate the possible role of the social media applications in promoting and developing both the motivation and listening skill of Iraqi EFL learners at an academic environment. As a case study, seventy-majoring English sophomores at Mustansiriya University in Iraq were randomly divided between two groups, experimental and control groups. The pretest and posttest were conducted to the participants of the study based on a curriculum assigned to them to be taught throughout their academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In a similar vein, Dirjal et al's study explore the potential role of Skype in developing listening motivation and listening skills. The finding reveals offering a real-like communication context: an instant conversation between interlocutors, Skype helps learners overcome language anxiety and thus facilitates listening practice [22].…”
Section: Speaking and Listeningmentioning
confidence: 95%
See 1 more Smart Citation
“…In a similar vein, Dirjal et al's study explore the potential role of Skype in developing listening motivation and listening skills. The finding reveals offering a real-like communication context: an instant conversation between interlocutors, Skype helps learners overcome language anxiety and thus facilitates listening practice [22].…”
Section: Speaking and Listeningmentioning
confidence: 95%
“…For example, social media are embedded with interesting content and fascinating functions, which may present as an obstacle for learners to focus on learning. Indeed, in documenting an attempt to incorporating writing activities into online social media platforms, it is reported by Dirjal et al that sometimes students may forget their online assignments and be distracted by other things on Internet [42]. Moreover, online correction checkers are originally designed to enhance working and interaction efficiency for learners.…”
Section: Limitations Of Social Mediamentioning
confidence: 99%
“…Other example is conducted by Dirjal et al (2020). The study is designed to answer the following: (1) Is the designed motivation questionnaire valid and reliable?…”
Section: Example Of Experimental Researchmentioning
confidence: 99%
“… Xodabande (2017) also argued that the proper use of social media can enhance learners’ interests and motivation, facilitate students’ access to target language input, provide them with more interaction opportunities and feedback and also give the instructors the tools they need to organize course content. Dirjal et al (2020) investigated the possible role of social media, particularly Skype, in promoting and developing learners’ motivation for language use. They found that male and female learners were highly motivated after receiving their instruction via Skype device.…”
Section: Literature Reviewmentioning
confidence: 99%